Preliminary Needs Assessment for the Development of an Effective Drill-Based Deep Learning Textbook for University Students - Subhan; Salahudin; Mariamah; Muhammad (Widya Accarya, 2025)
This study aims to analyze students' needs regarding the development of an Islamic Religious Education (PAI) textbook designed based on deep learning and drill strategies. The background of this research is rooted in the importance of instructional materials that can promote deep understanding, critical thinking, and problem-solving skills through structured exercises. This study employs a quantitative descriptive approach using a survey technique involving 45 student respondents. Data were gathered through a 4 point Likert scale questionnaire comprising 10 items and analyzed through descriptive statistical methods. The findings indicate that students' highest needs relate to textbooks that can guide them from basic concepts to solving complex problems (mean score: 3.44), as well as the inclusion of open-ended questions that stimulate critical thinking (mean score: 3.42). On the other hand, aspects such as the weaknesses of current textbooks and the one-way lecture method received lower average scores. Overall, students expressed a strong need for textbooks that are systematic, reflective, and contextual. Therefore, the results of this study recommend the development of a PAI textbook based on deep learning and drill as an innovative solution to improve the quality of Islamic Religious Education learning in higher education.